Proposal for The Management System for Domestic Solid Waste in The Waorani Gareno Community of The Ecuadorian Amazon - Vélez, Alberto Germán (2019)
The Waorani Gareno community, located in the rural parish Chonta Punta of the Napo province, Ecuadorian Amazon, has presented an increase in the generation of solid waste mainly due to the opening of roads for the settlement of the company’s 21 block oil field Ecuadorian operator Petroamazonas EP, which has caused greater access to goods and services provided in cities, changing their way of life and generating a new type of waste. In this work, the dynamics of generation and daily per capita generation of solid waste (PCGW) in the community were determined using the methodology used for the analysis of solid waste established by the Pan American Health Organization (PAHO). For this activity, the entire population was considered as a sample, that is to say, the 174 inhabitants distributed in 32 homes and the results were that the burning of waste is the main process for its disposal and that there is no adequate management system for the same. The calculated per capita waste generation was 0.26 kg /inhab/day with a total daily generation of 45.39 kg, which demonstrates a low population access to urban materials and products. Regarding the physical characterization of the residues, it was determined that the majority corresponds to organic content with 74.8%, and the inorganic part usable at 18.1%. In addition, from the results obtained, alternatives for collection, transport, treatment and final disposal of solid waste in the Gareno community were proposed, within the design of a waste management system.